Детали машин: учебное пособие - Добровольский В. А. Виктор Афанасьевич; Заблонский К. И. Константин Иванович; Мак С. Л. Соломон Львович; Радчик А. С. Александр Семенович; Эрлих Л. Б. Лазарь Борисович (Москва, Машиностроение, 1962)
На англ. яз.